Evaluating the Efficacy of Oral Ivermectin on Clinical Symptoms and Demodex Densities in Patients with Demodicosis - Paichitrojjana A; Chalermchai T (Dove Medical Press, 2024)
Anon Paichitrojjana, Thep Chalermchai School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, Bangkok, ThailandCorrespondence: Thep Chalermchai, School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, Khlong Toei Nuea, Watthana, Bangkok, 10110, Thailand, Email thep_chalermchai@hotmail.comBackground: Dermatologists consistently face challenges in treating demodicosis due to its high recurrence rate and difficulty normalizing the Demodex density (Dd) even after clinical improvement. Oral ivermectin has proven to be an effective treatment for demodicosis. However, there is a lack of comprehensive information on the clinical and acaricidal effects of oral ivermectin in treating demodicosis.Purpose: This study aims to evaluate the effectiveness of oral ivermectin on clinical symptoms and Dds of patients with demodicosis.Methods: This prospective, quasi-experimental study included 40 demodicosis patients (20 with Demodex densities (Dds) < 20 D/cm2, 20 with Dds ≥ 20 D/cm2). Both groups of patients were treated with oral ivermectin (200 μg/kg/week) until excellent clinical improvement (Grade 4 according to the Quartile Grading Scale), and Dds ≤ 5 D/cm2 or treated with oral ivermectin for a total of eight weeks period.Results: In our study, 75% of patients achieved clinical remission, showing excellent clinical improvement with Dds ≤ 5 D/cm2. All patients with a Dds < 20 D/cm² experienced remission, while 50% with a Dds ≥ 20 D/cm² achieved remission. The median time to remission after oral ivermectin treatment was 28 days for Dds < 20 D/cm² and 56 days for Dds ≥ 20 D/cm² (p < 0.001).Conclusion: Oral ivermectin effectively improves clinical symptoms and normalizes Dds in patients with demodicosis. Patients with higher Dds require a longer treatment than those with lower Dds.Keywords: ivermectin, demodicosis, Rosacea, Demodex mite, Demodex folliculorum, Demodex brevis